1990
DOI: 10.1016/0301-4622(90)85005-q
|View full text |Cite
|
Sign up to set email alerts
|

A time-resolved fluorescence study of human copper-zinc superoxide dismutase

Abstract: Superoxide dismutase; Time-resolved fluorescence: Fluorescence lifetime distribution; (Human)The intrinsic fluorescence decay of human Cu,Zn superoxide dismutase was measured by frequency-domain techniques. The protein consists of two subunits, each containing one tryptophsn and no tyrosine residues. Using a synchrotron radiation source, which allows facile selection of the excitation wavelength, the dependence of the emission decay upon excitation was studied. No significant excitation wavelength effects were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…Increasing temperature decreased both the average lifetime and the heterogeneity of the decay (width of the lifetime distribution). Similar temperature effects have been described for the homologous protein, human SOD (Rosato et al, 1990b), and for whiting parvalbumin (Ferreira, 1989). In those studies, the behavior of the width of the lifetime distribution as a function of temperature has been explained in terms of a temperature effect on the rates of interconversion between conformational substates in the proteins.…”
Section: Discussionsupporting
confidence: 52%
“…Increasing temperature decreased both the average lifetime and the heterogeneity of the decay (width of the lifetime distribution). Similar temperature effects have been described for the homologous protein, human SOD (Rosato et al, 1990b), and for whiting parvalbumin (Ferreira, 1989). In those studies, the behavior of the width of the lifetime distribution as a function of temperature has been explained in terms of a temperature effect on the rates of interconversion between conformational substates in the proteins.…”
Section: Discussionsupporting
confidence: 52%
“…A significant fluorescence quenching for the holo- compared with the apo-SOD1 protein has already been reported in the literature (44). Although most of the fluorescence quenching effects reported in literature are ascribed to the Cu(II) ion, it has been reported that the effect induced by Cu(I) ion is the same as the one induced by Cu(II) ion, as for instance reported for the type 1 copper protein azurin (45).…”
Section: Resultsmentioning
confidence: 60%
“…Fluorescence emission spectra of native and metal-depleted HSOD are structureless, centered at 344 nm, and similar to the spectrum of N-acetyltryptophanamide (NATA) [25]. The relative fluorescence intensity of holo and apo protein at 344 nm is reported in Figure l(a) as a function of GdHCl or urea concentration.…”
Section: A Steady-state Measurementsmentioning
confidence: 70%